Catalyst-free one-step synthesis of ortho-tetraaryl perylene diimides for efficient OPV non-fullerene acceptors. Issue 11 (2nd March 2017) - Li, Xiangchun; Wang, Hengbin; Schneider, Julia A.; Wei, Zitang; Lai, Wen-Yong; Huang, Wei; Wudl, Fred; Zheng, Yonghao
Abstract : We report the regioselective ortho -functionalization of PDI with aryl Grignard reagents. OPVs with these non-fullerene acceptors showed PCEs up to 5%, the highest reported for an acceptor with a single PDI core. Abstract : ortho -Functionalized perylene diimides (PDIs) display better electronic properties than their bay-substituted counterparts, yet their synthesis requires expensive catalysts. We report the regioselective 2, 5, 8, 11-functionalization of PDI via the less commonly observed 1, 4-addition of aryl Grignard reagents. This direct functionalization offers a simple and low-cost method to synthesize desirable ortho -substituted PDIs. Four tetraarylated PDIs are reported along with their electronic and optoelectronic properties. Preliminary organic photovoltaic devices using these molecules as non-fullerene acceptors showed good power conversion efficiencies (PCEs) up to 5%, a new record for an acceptor with a single PDI core.